Identidade e consumo em “modo super”: festivais de música pop pela perspectiva de fãs - Souza, Rodrigo Marcelo de (2026)
This study emerges from an interest in the phenomenon of popularity surrounding pop music festivals, as evidenced by box office records, media visibility, and substantial marketing and sponsorship investments. These events are examined from the perspective of reception, relating logics of communication and practices of consumption to processes of identity formation. By analyzing material and symbolic consumption within the context of festivals, the study discusses the centrality of communication and visibility in contemporary culture, shifting the focus from traditional advertising to the symbolic processes produced through experience and reception. Communication is understood not merely as media, but as the social phenomenon through which the common is culturally constructed, with communication-consumption operating as the privileged binomial through which subjects create and express an image of themselves, articulating affective ties, interests, affiliations, and aspirations. Although the sale and acquisition of commodities are relevant, the focus lies on the process through which production and consumption are socially constituted and legitimized. Based on theoretical research and empirical investigation, this dissertation aims to analyze how pop music fans who attend festivals articulate practices of consumption and communication in the constitution and affirmation of their cultural identities. The empirical stage was conducted through semi-structured interviews with self-identified fans who regularly attend large-scale festivals, selected according to criteria of active engagement in fandom practices and frequent participation in such events. The qualitative approach is justified by the need to understand the meanings attributed by the subjects themselves to their experiences, privileging the perspective of reception. The collected material was submitted to interpretative content analysis, articulating theoretical categories related to identity, consumption, and media culture with categories emerging from the empirical corpus. In summary, the findings indicate that these fans’ identity formation is linked to significant material and symbolic investments, to the incorporation of signs associated with pop culture, and to ongoing negotiations with artists and brands present at festivals. Although such events are often perceived as spontaneous cultural experiences, the analysis suggests the presence of mediations structured by market logics, even as they are negotiated at the level of reception.